Malunited capitellum fracture treated with corrective osteotomy, headless screws and interposition arthroplasty - A rare case report - Akash Kumar Ghosh; Deepak Kumar Negi; Vivek P. Ksheerasagar; Himanshu Bhayana; A.S. Sunil Kumar (Journal of Orthopaedic Reports, 2023)
Background: Capitellum fractures are a rare entity. These types of fractures are usually treated by open reduction and internal fixation with the help of headless compression screws. However, neglected or mismanaged fractures are prone to malunion or non-union and cause a bony block to elbow flexion. This has been historically managed with fragment excision or radio capitellar arthroplasty. However, the excision of capitellar fragment carries the risk of subsequent posterolateral instability of the elbow. Here, we present a novel treatment strategy for managing type IV capitellum fracture malunion and thinned articular cartilage with corrective osteotomy, headless screw and interposition arthroplasty. Case report: We report a case of 23 years old woman with 7 months old neglected capitellum fracture with malunion, treated with osteotomy of malunited fragment and open reduction and internal fixation (ORIF) with 3.2mm herbert screws. Interposition arthroplasty was added due to doubtful integrity of articular cartilage intra-operatively. At the final follow-up, painless elbow flexion from 15 to 90° was achieved with an excellent Mayo Elbow Performance score of 95. Conclusion: Neglected/malunited capitellum fractures are usually managed with excision of the fragment with a high incidence of postero-lateral instability of the elbow. The above treatment can be a viable option for patients with good results.